Economic and Energy Analysis of Building Retrofitting Using Internal Insulations - Małgorzata Basińska; Dobrosława Kaczorek; Halina Koczyk (Energies, 2021)
The energy-saving requirements for most buildings focus on improving the insulation and airtightness of a building’s envelope. In this paper, the authors have investigated the effect of additional internal insulation on energy consumption for heating and cooling in a residential building. Energy performance analyses were conducted for buildings with four internal thermal insulation systems in three locations using the WUFI Plus software. The Global Cost Method and Simply Pay Back Time have been used to assess and compare the economic viability of the retrofit systems. The results show that, in relation to energy, retrofitting with internal wall insulation can be an alternative to traditional external insulation. The assessment of internal insulation for low-energy buildings, however, cannot be conducted based on economic criteria. The usual approach of Simply Pay Back Time has exceptionally long payback time, which is unacceptable. In turn, the Global Cost Method, can only be used to compare the applied materials. With high investment costs, thermo-modernization improvements do not contribute to significant savings. The conditions of thermal comfort and the analysis of temperature and steam pressure play a decisive role in assessing this type of solution.